The Hypoellipticity and Parametrices for a Class of Nonprincipal Type LPDOs (Journal of Partial Differential Equations, 2020)
In this paper, we employ the method of increment operators, by means of the left invariant operators &#163^{v,s} on nilpotent Lie group G^{d_1+d_2} and the calculus of v- &PsiDOs, to discuss the hypoellipticity for a class of nonprincipal type LPDOs &#163 on a d_1 + d_2 dimensional manifold M. For those hypoelliptic &#163 we also construct their parametrices.